U–Pb zircon geochronology and phase equilibria modelling of a mafic eclogite from the Sumdo complex of south-east Tibet: Insights into prograde zircon growth and the assembly of the Tibetan plateau - Weller, O; St-Onge, M; Rayner, N; Waters, D; Searle, M; Palin, R (Elsevier, 2015)
The Sumdo complex is a Permian–Triassic eclogitic metamorphic belt in south-east Tibet, which marks the location of a suture zone that separates the northern and southern Lhasa terranes. An integrated geochronological and petrological study of a mafic eclogite from the complex has constrained its tectonometamorphic history and provides a case study of zircon growth in eclogite as a product of prograde dissolution–precipitation. In situ U–Pb geochronology indicates that the eclogite contains a single population of zircon with a crystallisation age of 273.6 ± 2.8 Ma. The morphology and chemistry of the zircon grains are consistent with growth by dissolution–precipitation of protolith magmatic zircon. The presence of zircon grains as inclusions in the cores of peak phases indicates that zircon dissolution–precipitation occurred during prograde metamorphism, and calculated pressure and temperature conditions over which mineral inclusions in zircon are stable suggest that the zircon most likely precipitated at ~15.5–16.5 kbar and 500–560 °C. Subsequent peak metamorphism is calculated to have reached pressure–temperature conditions of 27 ± 1 kbar and 670 ± 50 °C. Previous studies, which have documented a range of peak metamorphic conditions from high- to ultrahigh-pressure at c. 266–230 Ma, indicate that the Sumdo complex is a composite belt that experienced protracted eclogite exhumation. The results of this study are consistent with this interpretation, and extend the age range of high-pressure metamorphism in the complex to over 40 Myr. Analysis of published pressure–temperature–time data indicates two systematic behaviours within this spread. First, peak metamorphic temperatures declined over time. Second, eclogite exhumation occurred in two discrete intervals: soon after formation, and during the demise of the subduction zone. The latter behaviour serves as a reminder that eclogite exhumation is the exception rather than the rule.